Egy megyei romakutatás főbb eredményei (Szociológiai Szemle, 2024)
This study summarizes the results of a research conducted on the Romany community in the county Szabolcs-Szatmár-Bereg, in Hungary. The aim of this research was to create a database of empirical data to be used at different social programs in the county. The researchers have targeted to handle the various qualification methods integrally; with other words, besides the qualification of the majority they also applied the identification of the Romany community itself. In addition, the opinion of Romany professionals and the members of the local minority council were taken into account as well. The scope of this research addressed two main topics: the educational background of the Romany students and some aspects of the living conditions of the Romany community in the county. This latter research was based on a survey interviewing a sample of 1005 households.The situation of the Romany community in the county was examined from different aspects: such as their socio-demographical situation, living conditions, economical activity and educational background, their perception of problems and their attitude on perspectives. The findings did not reveal any significant differences to the overall situation in Hungary concerning many of these aspects; thus the major figures in the county were similar to those determined in the country. In the contrary, the study revealed significant results on the field of the perception of problems and the attitude on perspectives. Among the youth there is an acceptance of the need of higher educational background, which is basically a desired trade school degree at this point. To learn the traditional Romany professions is not any more attractive. The Romany community considers unemployment as its most significant problem and poverty as a result thereof. They are despair and they are looking forward to being supported – similarly to other underclass groups – by the state and not by the local council or Romany societies, which are considered to be powerless.